Weak Expression of Terminal Complement in Active Antibody-Mediated Rejection of the Kidney - Tiller, Gesa; Lammerts, Rosa G. M.; Karijosemito, Jessy J.; Alkaff, Firas F.; Diepstra, Arjan; Pol, Robert A.; Meter-Arkema, Anita H.; Seelen, Marc. A.; van den Heuvel, Marius C.; Hepkema, Bouke G.; Daha, Mohamed R.; van den Born, Jacob; et al. (Frontiers in Immunology, 2022)
Background: The role of the complement system in antibody-mediated rejection (ABMR) is insufficiently understood. We aimed to investigate the role of local and systemic complement activation in active (aABMR). We quantified complement activation markers, C3, C3d, and C5b-9 in plasma of aABMR, and acute T-cell mediated rejection (aTCMR), and non-rejection kidney transplant recipients. Intra-renal complement markers were analyzed as C4d, C3d, C5b-9, and CD59 deposition. We examined in vitro complement activation and CD59 expression on conditionally immortalized endothelial cells upon incubation with human leukocyte antigen antibodies. Methods: We included 50 kidney transplant recipients, who we histopathologically classified as aABMR (n=17), aTCMR (n=18), and non-rejection (n=15). Results: Complement activation in plasma did not differ across groups. C3d and C4d deposition were discriminative for aABMR diagnosis. Particularly, C3d deposition was stronger in glomerular (P<0,01), and peritubular capillaries (P<0,05) comparing aABMR to aTCMR rejection and non-rejection biopsies. In contrast to C3d, C5b-9 was only mildly expressed across all groups. For C5b-9, no significant difference between aABMR and non-rejection biopsies regarding peritubular and glomerular C5b-9 deposition was evident. We replicated these findings in vitro using renal endothelial cells and found complement pathway activation with C4d and C3d, but without terminal C5b-9 deposition. Complement regulator CD59 was variably present in biopsies and constitutively expressed on renal endothelial cells in vitro. Conclusion: Our results indicate that terminal complement might only play a minor role in late aABMR, possibly indicating the need to re-evaluate the applicability of terminal complement inhibitors as treatment for aABMR.